Wirklichkeitsnah oder stereotyp? Das Bild von Dänemark und den Dänen in ausgewählten deutschen Lehrbüchern für Dänisch als Fremdsprache - Jarosz, Józef (Folia Scandinavica Posnaniensia, 2016)
The contemporary teaching of foreign languages assumes the development of the ability to use a foreign language in different communication situations. Apart from language competence, also the cultural competence is developed as it is a necessary component of communication. A successful transfer of knowledge and language skills in the process of foreign language learning is determined by a textbook (in addition to other factors). The goal of this article is to analyze the content and assess three Danish textbooks, which were published in Germany in the years 2008-2010. The textbooks are examined in terms of knowledge about Danish life and institutions, the transfer of intercultural competence and the presence of stereotypes. The textbooks were studied based on the list of criteria and it resulted in stating that the textbooks fulfill the objective of providing the knowledge about the country to a great degree. The intercultural component and the issue of stereotypes are dealt with in a different manner.